A new versatile x–y–z electrospinning equipment for nanofiber synthesis in both far and near field. - Calzado-Delgado, María del Mar; Guerrero-Pérez, María Olga; Yeung, King (Nature, 2022)
This work describes a versatile electrospinning equipment with rapid, independent, and precise x–y–z movements for large-area depositions of electrospun fibers, direct writing or assembly of fibers into sub-millimeter and micron-sized patterns, and printing of 3D micro- and nanostructures. Its versatility is demonstrated thought the preparation of multilayered functional nanofibers for wound healing, nanofiber mesh for particle filtration, high-aspect ratio printed lines, and freestanding aligned nanofibers.
Keywords: Nanoestructuras; Fibras - Fabricación; Electrospinning